Long transparent cap-assisted clip closure technique: a new choice for gastrointestinal defect closure - Nan Dai; Changqing Guo; Shanshan Zhu; Saif Ullah; Jingwen Zhang; Ping Liu; Fangbin Zhang; Xinguang Cao (BMC Gastroenterology)
Abstract Objective To evaluate the safety and effectiveness of the novel long transparent cap-assisted clip closure technique in closing gastrointestinal defects. Methods A retrospective analysis was performed on clinical data of patients who underwent endoscopic resection for gastric submucosal tumors at the First Affiliated Hospital of Zhengzhou University from January 2020 to November 2023. Patients were categorized into the Long Transparent Cap-Assisted Clip Closure group (LTCCC group) and the Purse-String Suture group (PSS group) based on the method of wound closure after ER. Primary outcomes included closure success rates and closure time, and secondary outcomes covered postoperative hospital stays, occurrence of adverse events, tumor characteristics, and follow-up status. Results The closure success rate was 100% in both groups. The closure time in the LTC group was shorter than that in the PSS group (17.44 ± 7.71 min vs. 28.81 ± 9.20 min, P < 0.001). There were no statistically significant differences in postoperative hospital stays and adverse event rates between the two groups (P > 0.05). Good wound healing was observed during follow-up. No residual lesions, tumor recurrence, metastasis, gastrointestinal fistulae, or sinuses were found during a median follow-up of 32 (5 ~ 73) months. Conclusion The long transparent cap-assisted clip closure technique is a simple, safe, and effective method for closing gastrointestinal defects, and can be considered as a treatment option for endoscopic closure of such defects.